Legal Analysis Of The Exclusion Of A Creditor From The Final Creditor's List - Sihombing, Sherina Elizabeth; Debora, Debora; Sidauruk, Jinner (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study aims to analyze the legal actions that can be taken by creditors who are excluded from the final creditor's list and assess the legal consequences of a bankruptcy ruling if the Renvoi Procedure is granted. The research was conducted using a normative juridical approach through a literature study of primary and secondary legal materials, including Law No. 37 of 2004 on Bankruptcy and Suspension of Debt Payment Obligations, court decisions, and expert opinions. A qualitative analysis technique was employed to interpret the norms, legal principles, and settlement practices in bankruptcy proceedings. The research findings indicate that a delay in submitting a claim by a creditor results in the rejection of that claim by the curator, causing the creditor's rights to be disregarded in the distribution of the debtor's assets. The Renvoi Procedure, as a legal mechanism available, provides the creditor with an opportunity to file an objection so that the rejected claim can be reinstated, without altering the status of the bankruptcy ruling that is binding on all creditors. Therefore, this study concludes that the Renvoi Procedure is an effective tool to address injustice in bankruptcy processes while ensuring the protection of creditor rights.